Kebijakan Afirmatif Pengadaan Barang/Jasa Pemerintah Di Wilayah Papua Ditinjau Dari Hierarki Peraturan Perundang-Undangan - Yudha, Unggul Hangga; Warman, Kurnia; Andora, Hengki (Nagari Law Review, 2024)
The affirmative policy allowing the State to do more to the unrepresented group within the framework of equality and justice is enshrined in Article 28 H (2) of the Constitution of the Republic of Indonesia of 1945 which states that everyone is entitled to special facilities and treatment for equal opportunities and benefits in order to equity and justice. In the government procurement through providers, the Papua Special Autonomy Act forms the basis for the affirmative policy to be established. The study aims to analyze the existence of affirmative policy of government procurement through providers and to examine the content of the article according to the hierarchy of the regulations. The study uses a normative and descriptive approach, legal research to describe and test applicable norms or provisions. Research results: First: the affirmative policy of government procurement through providers requires the existence of the participation of papuan economic operator directly in government procurements through providers in the territory of Papua, where the criteria of Papuan economic operator have also been set out in the regulations. Secondly, in the content of Article 2 of the Papua Governor Regulation Number 46 of 2021 on Government Procurement in Papua Province, it is explained that the scope of application of the governor's regulation includes the government procurement financed by the State Budget Funds. This is contrary to the content of article 4 Paragraph (1) letter a of the Regulation of the Minister of Public Works and Housing No. 1 of 2023 on the Guidelines for the Supervision of the Maintenance of Construction Services Implemented by the Provincial Government, the District, and the City which explains that the authority of the local government of the provinces, the districts and the towns in supervising the maintenance of the construction services, including the process of government procurement, is limited only to the activities of construction financed with the Regional Budget Funds.